2007
DOI: 10.1016/j.ijresmar.2006.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Consumer confidence in Europe: United in diversity?

Abstract: The ongoing unification taking place in the European political scene, along with recent advances in consumer mobility and communication technology, raises the question of whether the European Union can be treated as a single market to exploit potential synergy effects from panEuropean marketing strategies. Previous research, which mostly used domain-specific segmentation bases, has resulted in mixed conclusions.In this paper, a more general segmentation basis is adopted, as we consider the homogeneity in the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 76 publications
(107 reference statements)
2
38
0
Order By: Relevance
“…We therefore expect national context to have a clear effect on the strength of the relationships described by our conceptual framework. This is consistent with research in other areas that has demonstrated that new product growth patterns (Stremersch & Tellis, 2004) and even Consumer Confidence Indicators (Lemmens, Croux, & Dekimpe, 2007) differ substantially across different European regions.…”
Section: Conceptual Frameworksupporting
confidence: 90%
“…We therefore expect national context to have a clear effect on the strength of the relationships described by our conceptual framework. This is consistent with research in other areas that has demonstrated that new product growth patterns (Stremersch & Tellis, 2004) and even Consumer Confidence Indicators (Lemmens, Croux, & Dekimpe, 2007) differ substantially across different European regions.…”
Section: Conceptual Frameworksupporting
confidence: 90%
“…For consumer confidence we used the consumer confidence index, provided by the Directorate General Economy and Finance (DG ECFIN) of the European Commission. This scale has previously been used by Lemmens, Croux, and Dekimpe (2007) and is highly similar to the consumer confidence scales in Nijkamp et al (2002) and Van Raaij and Gianotten (1990). The consumer confidence scale consists of two parts.…”
Section: Datamentioning
confidence: 99%
“…Current research on unit-root tests using wavelets shows promise in increasing power, especially when analyzing near unit-root alternatives (e.g., Fan & Gençay, 2010). Although wavelets have been previously used in marketing to study time-series properties in the frequency domain (Lemmens, Croux, & Dekimpe, 2007), their use in unit-root testing is less developed and is a promising area for future research.…”
Section: Resultsmentioning
confidence: 99%